Detection and Prevalence of Macrolide and Fluoroquinolone Resistance in Mycoplasma genitalium in Badalona, Spain - Belén Rivaya; Chloé Le Roy; Elena Jordana-Lluch; Gema Fernández-Rivas; Cristina Casañ; Victoria González; Jun Hao Wang-Wang; Cécile Bébéar; Lurdes Matas; Sabine Pereyre (MDPI AG, 2022)
Macrolide and fluoroquinolone resistance (MLr/FQr) in Mycoplasma genitalium (MG) infections is concerning worldwide. Current guidelines recommend performing MLr detection in MG-positive cases to adjust antimicrobial therapy. We aimed to evaluate the usefulness of PCR followed by pyrosequencing for MLr detection in comparison with a one-step commercial assay and to assess the prevalence of MLr and FQr in Badalona, Spain. A total of 415 MG-positive samples by Allplex STI-7 (Seegene) were analyzed for MLr detection by pyrosequencing. From those, 179 samples were further analyzed for MG and MLr by ResistancePlus® MG kit (SpeeDx) and 100 of them also for fluoroquinolone resistance (FQr) by sequencing the parC gene. Regarding MG detection, Allplex and Resistance Plus® showed an overall agreement of 87%, but this value rose to 95.4% if we compare them for MLr detection. Prevalence of MLr was 23.1% in Badalona, but this rate increased to 73.7% in the HIV-positive patients cohort. FQr detection showed 3% of resistant strains. Pyrosequencing is a convenient and cheap technique for MLr detection, but one-step tools should be considered in high-throughput laboratories. Despite the fact that MLr remained moderate and FQr was low in our study, simultaneous MG and MLr detection would improve patient's management applying resistance-guided treatment strategies.